Online-Offline in Religion; Observing Islamic Learning Patterns in Online Media - Achmad Muhibbin Zuhri; Jauharoti Alfin (Tribakti: Jurnal Pemikiran Keislaman, 2022)
This study aims to unravel the phenomenon of digital society in understanding and learning Islam through the internet. The current human tendency to rely on information available through smartphones has given birth to the reality of shifting learning patterns that do not have to meet directly with the teacher. Even the presence of a virtual teacher is considered sufficient to justify an excellent religious way. This study uses a qualitative method with a netnographic approach that intends to reveal social phenomena in cyberspace. This method uses a particular analytical technique offered, AMS (Siber Media Analysis), which goes through 4 levels: Media room level, media document level, media object level, and experience level. This study found that online internet users can access information about religious rituals and procedures for doing them. So, internet users are part of the world's religious adherents who carry out the same religious creed. On the other hand, religious authority as a source of knowledge in learning Islam on the internet is not always institutional but can also be individual. As a result, the Islamic pattern of understanding Islam among netizens is more accessible, inclusive, egalitarian, and shows multidimensional interactions between individuals and other religious groups.